PENGENDALIAN KAWASAN PERMUKIMAN PERKOTAAN DI KAWASAN KONSERVASI KECAMATAN BOGOR SELATAN - Maskawan Siahaan; Soekmana Soma; Zefri Zefri (Universitas Indraprasta PGRI, 2019)
The South Bogor District which is a conservation area who has a function and the role of conservation area and land that can provide portection for the area of his men, and is the settlement with congestion low. But the development of the settlement within 10 years, from the 2007-2016 has resulted in the change in the use of the land in this area of 481,91 Ha or an average of 48.19 Ha/year. The purpose of this research is composed a strategy that needs to be done to control the develop housing area, so that the existence of a conservation are stay awake. Methods used is method superimpose and scoring then do the factors that most influential on the aberration of utilization of land. From the analysis of the level of threat is conservation areas, most of the area included in the middle classification with an area of 938.58 Ha (46.55 %), a high threat level of 283.30 Ha (14.05%), while low threat level with an area reaching 794.26 Ha (39.40%). In addition, from the overlay of the spatial pattern map contained in the RTRW with the existing conditions, it shows existence land use mismatches specified in the spatial plan an area of 1,662.40 Ha or 59.77%. The factors that cause the change in land use in this conservation area are population development, socio-economic conditions, accessibility, supervision of settlement construction, and licensing problems. Output the study of internal factors and external factors is conducted then a strategy can be done improve the supervision of development involving with communities by cracking down on violations of the utilization of space in the area that are not in accordance with the spatial plans, as well as maintain and preserve conservation areas through the housing development that environmentally.